Microbial Fuel Cell Technology: Power Generation Using Various Wastewater Sources - S. D. Purswani; S. S. Atkare; G. Bhumkar; M. B. Patil (Research Highlights in Science and Technology Vol. 6, 2023)
The escalating risk of global warming, driven by greenhouse gas emissions, necessitates urgent advancements in renewable energy sources. Among these sources, microbial fuel cells stand out as a promising electrochemical technology capable of harnessing energy from diverse wastewater streams. These fuel cells leverage the catalytic activity of living microorganisms to convert the chemical energy present in organic matter into electricity. This study explores the application of microbial fuel cells to recover energy from three distinct waste sources: dairy wastewater, sewage wastewater, and urine. Proton exchange membranes were employed as electrolytes during experimentation. Notably, the open circuit voltage measurements revealed encouraging results. Dairy wastewater yielded an observed voltage of 0.26V, while sewage wastewater exhibited a higher voltage of 0.46V. Surprisingly, urine demonstrated a comparable open circuit voltage of 0.42V. By converting organic matter into electricity through the catalytic activity of microorganisms, microbial fuel cells offer a promising avenue to address the pressing challenges posed by global warming and greenhouse gas emissions.